4-Cyanobenzaldehyde thiosemicarbazone - Wu, De-Hong (International Union of Crystallography, 2008)
The molecule of the title compound, C(9)H(8)N(4)S, adopts an E configuration about both the C=N and C—NH bonds. In the crystal structure, adjacent molecules are linked by intermolecular N—H⋯S hydrogen-bonding interactions, forming chains running parallel to the b axis.